Land rights and land conflicts in Kibaale since the colonial settlement - Baligira, John (African Studies, 2020)
This thesis examines why there has been persistent conflict over land in Africa, with reference to Kibaale district in western Uganda. The land conflicts, especially in post-colonial sub-Saharan Africa, are attributed to such factors as the colonial legacy which has contributed to unequal access and conflicting identities. By tracing the conflict from the British colonial period, the thesis contributes to an understanding of how it evolved and why it was not resolved by the end of colonial rule and in post-colonial Uganda. The thesis draws on Mamdani's theory of decentralized despotism to establish the extent to which the post-colonial central governments' maintenance of some rural despotic authorities has undermined the land conflict resolution efforts. I contend that, though the post- colonial governments' maintenance of landlordism has partly contributed to the land-related conflict in Uganda, it does not fully explain why the conflict has persisted in places such as Kibaale district. Based on data generated through in-depth interviews with purposively sampled participants, archives and from secondary sources, the thesis contributes to an improved understanding of why land-related conflicts in Africa have persisted. It particularly shows what has undermined the ability of post-colonial governments and other stakeholders to address the roots of these conflicts. The main findings of the thesis include: the bitter memories of the late 19th and early 20th century British colonial conquest and land dispossession of people in Kibaale are still reflected in the narratives of the early settlers; the government-sponsored and selfmotivated massive resettlement of people from mainly Western Uganda to Kibaale district has increased the complexity of land disputes; different peoples' identities have also contributed to the conflict in Kibaale; and the national as well as local political actors have often intensified the conflict for the sake of political power. The thesis concludes that the instrumentalization of citizenship and belonging by the autochthons as well as the specific historical and socioeconomic factors in Kibaale district have contributed to persistent conflict over access to and ownership of land.